Pouca saúde e muita saúva, os males do Brasil são! O povo em Macunaíma, o herói sem nenhum caráter, de Mário de Andrade - Menezes, José Lúcio da Silva (2018)
This dissertation examines the ethnic and cultural diversity of the Brazilian people in Mario de Andrade’s work Macunaíma - a consecrated literature work that has been object of numerous other investigations. A specific inquiry gave the north to this research: could Macunaíma's character be taken as an expression of a given representation of the Brazilian people? An issue that problematizes Mario de Andrade rhapsody, because the main character was enshrined as an emblem of national identity that was a concern of the nationalism at that time. Macunaíma was noted for his uncharacteristic characteristics attributed to him by the modernist author: hero without character, selfish, with exaggerated sexuality, lazy and very astute. The National identity that was part of the debates proposed by the modernists during of the Modern Art Week of 1922 had as objective to recover the popular culture. Thus Macunaíma, which is the result of an intense research on Brazilian people culture, accomplishes, in some way, the yearnings of that movement